Sistema automático de irrigação autônomo de baixo custo - Pereira, Bruno Williams Antunes (Universidade Federal de São Carlos, 2023)
This work aims to develop a low-cost automated irrigation system. The system employs an Arduino and sensor to continuously monitor soil moisture levels. When soil moisture reaches a predefined threshold, an irrigation mechanism, triggered by a solenoid valve, comes into operation. This irrigation process is maintained until the soil moisture reaches a new desired level, at which point the system automatically interrupts the water supply. It is important to note that this system operates autonomously in terms of energy, since its components are powered by a solar panel, ensuring its sustainability and energy efficiency. This work covers a variety of topics related to irrigation, including the principles and methods associated with this agricultural practice. In addition, it describes in detail the operation of the components used. The assembly process is described, providing a comprehensive overview of how the system is built and implemented. With regard to the financial aspect, this project has an estimated average cost of 170 reais. This includes all of the components and materials necessary for the effective assembly and operation of the automated irrigation system.
Low cost automatic autonomous irrigation system
Keywords: Sistema de irrigação; Irrigation system; Sistema autônomo; Autonomous system; Energia solar; Solar energy; Internet das coisas; Internet of things; IoT; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::SISTEMAS DE COMPUTACAO